A New Account of Replication in the Experimental Life Sciences. Issue 3 (July 2019) - Guttinger, Stephan
Abstract : The life sciences are said to be in the midst of a replication crisis because (1) a majority of published results are irreproducible, and (2) scientists rarely replicate existing data. Here I argue that point 2 of this assessment is flawed because there is a hitherto unidentified form of replication in the experimental life sciences, which I call 'microreplications' (MRs). Using a case study from biochemistry, I illustrate how MRs depend on a key element of experimentation, namely, experimental controls. I end by reflecting on what MRs mean for the broader debate about the replication crisis.